2020
DOI: 10.1099/mic.0.000886
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines produced by Sinorhizobium meliloti Rm8530 contribute to symbiotically relevant phenotypes ex planta and to nodulation efficiency on alfalfa

Abstract: In nitrogen-fixing rhizobia, emerging evidence shows significant roles for polyamines in growth and abiotic stress resistance. In this work we show that a polyamine-deficient ornithine decarboxylase null mutant (odc2) derived from Sinorhizobium meliloti Rm8530 had significant phenotypic differences from the wild-type, including greatly reduced production of exopolysaccharides (EPS; ostensibly both succinoglycan and galactoglucan), increased sensitivity to oxidative stress and decreased swimming motility. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 57 publications
0
18
0
1
Order By: Relevance
“…We previously reported that exogenous polyamines affect biofilm formation, EPS production and motility in S. meliloti Rm8530 [36]. We hypothesized that these effects were at least partly due to the S. meliloti NspS-MbaA homologs acting as a polyamine sensing-transducing system to modulate biofilm formation in a manner analogous to the V. cholerae system [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that exogenous polyamines affect biofilm formation, EPS production and motility in S. meliloti Rm8530 [36]. We hypothesized that these effects were at least partly due to the S. meliloti NspS-MbaA homologs acting as a polyamine sensing-transducing system to modulate biofilm formation in a manner analogous to the V. cholerae system [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Individual colonies of the S. meliloti strains were stabbed into the swarming media with a toothpick and incubated at 30°C for 72 h. Swarm zones were quantitated by taking the average of two sides of a rectangle that framed the zone [35]. Swimming assays were performed in Bromfield medium containing 0.3 % Noble agar as described previously [36].…”
Section: Motility Assaysmentioning
confidence: 99%
“…Another strong paper from Michael Dunn's group at the Universidad Nacional Autónoma de México, Cuernavaca, Mexico, features in this issue, which is in fact the second from this group in 2020 (I might have to think of some kind of a prize) [10,11]. Continuing the theme of studying nitrogen metabolism in nitrogen-fixing bacteria, in this paper his group identify the arginase enzyme from Sinorhizobium meliloti, which is required for use of l-arginine as the sole nitrogen source by first breaking it down to l-ornithine and urea.…”
mentioning
confidence: 98%
“…The number of nodules was not reduced, but their function was poor, as reflected by decreases in plant weight and height. The authors think this nodule phenotype most likely results from the defects in EPS production, which likely underlie many of the other phenotypes, but the mechanism of this control is not known at present [4].…”
mentioning
confidence: 99%
“…In our first paper we focus on the α-proteobacterium Sinorhizobium meliloti , which forms root nodules in leguminous plants that mature to become little cell factories for fixing nitrogen gas, ultimately to organic nitrogen, whilst at the same time being fed by the plant. A new paper from Michael F. Dunn's group in UNAM, Mexico, examined the function of polyamines in the biology of this bacterium [ 4 ]. These are small polycations that are accumulated by bacterial cells for a variety of cellular functions, and which his group, working with my colleague Jane Thomas-Oates at York ( @ChemistryatYork ), had shown in 2018 were required for normal cell growth [ 5 ].…”
mentioning
confidence: 99%